LEGISLATIVE PROVISIONS FOR ADULT EDUCATION IN LITHUANIA - Zemaitaityte, Irena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article reviews the changes in legal acts and their role in the development of adult education in Lithuania. Developing learning opportunities and bringing educational services closer to each individual is a political action based on a fundamental provision of respect for the individual, his / her ability to create one's own life and that of his / her loved ones and the duty to help to do it as best as possible. Education, as an institution, has an increasingly complex role to play in justifying and creating a common educational content on which to build the social life of society in order to enable a person to develop general skills, lifelong learning skills, and helping him to adapt to a constantly changing environment. The laws and resolutions discussed reflect the advanced attitude of adult education in Lithuania as an important part of the lifelong learning system in society and provide wider opportunities for its development. Summarizing the normative documents regulating adult learning, it can be stated that at the level of strategic objectives they are relevant and purposeful, but not sufficient in some cases.